Pengaruh Pembuatan Terasering Pada Lereng Terhadap Potensi Longsor - Sumiyanto Sumiyanto; Adhe Noor Patria (Dinamika Rekayasa, 2010)
Indonesia is one country with the population growth rate is large. This condition will require the opening of new land for settlement. Limited land sometimes requires people to open new land on the slope areas. Opening of new land on the slopes will use the method of cutting the slope to get flat land (terrace). Cutting this slope would result in increased potential for landslides due to slope stability menurunya. Evaluation needs to be done at the opening of new land on the slopes, where the slope should remain stable after the porch is made. This research was conducted to evaluate the maximum terrace width was in stable condition. The model used in this study is a plane strain by the count to element method. The main purpose of this research is to obtain the maximum terrace width formula on a slope. Dilakukan analysis on three ).), cohesion, (c) and angle of internal friction (variables, namely slope( Variations to the variable angle between 30o-55o intervals 5o, 5 kN/m2 cohesion between-25 kN/m2 with intervals 5 kN/m2, and internal friction angle between 20o-45o intervals 5o. Maximum terrace width count conducted for each combination of these variables. Formulation of the maximum terrace width is done by multiple linear regression methods, linear nin and a combination of both. Determining the best formula is based on the value of the correlation koofisien. Results formulations have two formulasis the formula for the maximum slope of the natural slope and a maximum width of the terrace on a slope.